Media, zło i społeczeństwo. Wykorzystanie mediów i ich wpływ na postrzeganie przestępczości i postawy wobec polityki karnej - Pfeiffer Christian (Archiwum Kryminologii, 2006)
ln democratic societies, crime policy and its management by parliaments and ministries largely depends on trends in crime. If, over a prolonged period. the media report strong upward trends in the number of crimes committed and if the public clebate on crime focuses on spectacular, serious crimes, policymakers come under heavy pressure to increase statutory punishments and tighten the rules of procedure for criminal prosecutions. The courts in turn feel bound to hand out tougher sentences – passed in the name of the people, their judgements are meant to reflect public opinion. The question thus arises as to whether long periods of either dwindling or stable crime figures allow policymakers and the courts to soften punishments for specific offences and to place, for example, the notion of offender-victim compensation and offender resocialisation at the forefront.